L = lambda
x + 2y + Lz = 0
2x + 3y -2z = L
Lx + y + z = 3
in other problems like this i have solved using gaussion elimination where i would have used x in equation one as a pivot to get rid of the x's in the other two equations.
however the lambda in the equation has me stumped. how would i use the x to get rid of the Lx.
any help would be greatly appreciated
is there other methods for solving this problem
thanks
x + 2y + Lz = 0
2x + 3y -2z = L
Lx + y + z = 3
in other problems like this i have solved using gaussion elimination where i would have used x in equation one as a pivot to get rid of the x's in the other two equations.
however the lambda in the equation has me stumped. how would i use the x to get rid of the Lx.
any help would be greatly appreciated
is there other methods for solving this problem
thanks